King's vibrato : modernism, Blackness, and the sonic life of Martin Luther King Jr. - Wallace, Maurice O. (Maurice Orlando), 1967- (Duke University Press, 2022)
"King's Vibrato explores the sonic power of preaching and speech-making in the life and career of Martin Luther King Jr. It offers up a cultural and historical reading of what regularly passes uncritically as the unique preaching power of one who "spoke with the tongues of men and of angels," but which depends (in both predictable and surprising ways) on an acoustic calculus involving, but not reducible to, architecture, instrumentation, audience, and technology in oratorical performativity. Together, the acoustical considerations of ecclesial architecture in the US since 1900, the regular furnishing of aspirational African American church buildings with pipe organry, and African Americans' special relationship to speech and song created the conditions for that unique vibrato effect in King's voice with which he moved the world. In more general terms, King's Vibrato is a cultural history and critical theory of the black modernist soundscapes, North and South, that helped produce the vocal timbre and time signature of the preacher King"--